(untitled) (INNOVATIVE ECONOMY, 2025)
Nazarkevych I.B., Oliinyk O.I. THE INFLUENCE OF TAX POLICY ON THE FORMATION OF THE FINANCIAL SECURITY OF THE STATE IN THE CONDITIONS OF MARTIAL LAW Purpose. The aim of the article is to determine the influence of tax policy on the formation of Ukraine’s financial security in the conditions of martial law. Methodology of research. General scientific and specialized research methods were used, including: the dialectical method ‒ for the systematic study of the role of the tax service in ensuring the state’s financial security in the conditions of martial law; the monographic method ‒ for examining the specifics of tax policy in crisis conditions; methods of analysis and synthesis ‒ for a detailed study of sources of tax revenues and the main activities of the tax service; comparative analysis ‒ to compare tax revenues during 2021–2023. Findings. The study identified the impact of tax policy on Ukraine’s financial security in the conditions of martial law. It was established that the effective work of the tax service, the introduction of digital tools for tax administration, and temporary tax incentives partially offset the losses of the state budget. The analysis of tax revenues for 2021–2023 revealed key trends: a decrease in revenues in 2022 due to the crisis and their partial recovery in 2023 due to business adaptation to war conditions and changing market conditions. The calculation of fiscal security indicators showed an increase in the level of in fiscal stability, highlighting the effectiveness of the measures implemented. Recommendations are proposed to increase the effectiveness of state tax policy aimed at supporting economic stability in crisis conditions. Originality. For the first time, the causal relationships of the impact of tax policy on the formation of financial security in the conditions of martial law were substantiated, which, unlike existing approaches, allows for a more accurate assessment of the impact of tax decisions on the stability of the national economy. The approach to analyzing the structure and dynamics of tax payments and their nature in the conditions of martial law was improved, which allows for a comprehensive assessment of their nature and consequences for the fiscal sustainability of the state. The integration of data on tax revenues, budget deficit and debt burden for calculating the integral indicator of fiscal security of Ukraine has been further developed, which contributes to increasing the effectiveness of state tax policy in times of crisis. Recommendations for improving the efficiency of state tax policy were proposed. The research results emphasize the critical importance of tax policy for economic stabilization in crisis conditions. Practical value. The study’s findings can be used to develop financial security strategies in crisis conditions and support the stability of Ukraine’s state budget. Key words: tax service, financial security, martial law, tax policy, digitalization, tax administration, budget revenues, economic stability, tax incentives, electronic services, fiscal security.